"OKASAN" Onigiri Kaya Rasa Nusantara: Inovasi Pangan Lokal Sebagai Alternatif Menu Praktis Berenergi - Gahari, Raehana Saria (Program Kreativitas Mahasiswa - Kewirausahaan, 2014)
In the global era, people become busier, more active and more dynamic. High activity needs a balanced energy intake support from food. Therefore, people with high activity requires practical carbohydrate-rich foods, one of the solution is to pack the rice into Onigiri or rice balls typicalof Japanese. The concept of the product is very potential to be marketed, because we create the product innovation with the concept of Japan and archipelago nuanced, which is grilled Onigiri that contains a side dish with flavors typicalof the archipelago, such as rendang, satay Madura, and others. Okasan is made from high quality local rice combined with a stuffing meatballs, chicken, or mushrooms mixed with various flavors typical of the archipelago. This product is marketed at a price of Rp.4000, - until Rp.5000, - for general consumers and Rp.3500, - to the agent. The sales activity has been running for 4 months with revenues of Rp.3.155.000, -, and we have achieved BEP in a time of 1.5 months.Keywords : rice, practical, energy, Nusantara typical